Debt, deleveraging and business cycles: An agent-based perspective - Marco Raberto; Andrea Teglio; Silvano Cincotti (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
The recent financial crises pointed out the central role of public and private debt in modern economies. However, even if debt is a recurring topic in discussions about the current economic situation, economic modeling does not take into account debt as one of the crucial determinants of economic dynamics. The authors' contribution, in this paper, is to investigate the issues of borrowing and debt load by means of computational experiments, performed in the environment of the agent-based Eurace simulator. The authors aim to shed some light on the relation between debt and main economic indicators. Their results clearly confirm that the amount of credit in the economy is a very important variable, which can affect economic performance in a twofold way: fostering growth or pushing the economy into recession or crisis. The outcomes of their computational experiments show a rich scenario of interactions between real and financial variables in the economy, and therefore represent a truly innovative tool for the study of economics.
Keywords: E2; E3; E44; E51; 330; agent-based computational economics; debt; leverage; credit money; economic crisis; Schulden; Kreditgeschäft; Makroökonomischer Einfluss; Konjunktur; Kapitalstruktur; Agentenbasierte Modellierung; Simulation; Finanzmarktkrise; Theorie